Investigating the key principles in two-step heterogeneous transfer learning for early laryngeal cancer identification - Xinyi Fang; Chak Fong Chong; Kei Long Wong; Marco Simões; Benjamin K. Ng (Scientific Reports)
Abstract Data scarcity in medical images makes transfer learning a common approach in computer-aided diagnosis. Some disease classification tasks can rely on large homogeneous public datasets to train the transferred model, while others cannot, i.e., endoscopic laryngeal cancer image identification. Distinguished from most current works, this work pioneers exploring a two-step heterogeneous transfer learning (THTL) framework for laryngeal cancer identification and summarizing the fundamental principles for the intermediate domain selection. For heterogeneity and clear vascular representation, diabetic retinopathy images were chosen as THTL’s intermediate domain. The experiment results reveal two vital principles in intermediate domain selection for future studies: 1) the size of the intermediate domain is not a sufficient condition to improve the transfer learning performance; 2) even distinct vascular features in the intermediate domain do not guarantee improved performance in the target domain. We observe that radial vascular patterns benefit benign classification, whereas twisted and tangled patterns align more with malignant classification. Additionally, to compensate for the absence of twisted patterns in the intermediate domains, we propose the Step-Wise Fine-Tuning (SWFT) technique, guided by the Layer Class Activate Map (LayerCAM) visualization result, getting 20.4% accuracy increases compared to accuracy from THTL’s, even higher than fine-tune all layers.